Osnove potresnega inženirstva: Učbenik - Skrinar, Matjaž (University of Maribor Press, 2021)
Basics of Seismic Engineering: Textbook. Earthquake engineering is an extremely broad scientific and professional field, which has been intensively developing in recent years, and so it is impossible to gather all the knowledge in this field in a single volume. Although the topics covered in this work are related to the current Eurocode ENV 1998-1 standard, they are not limited exclusively to this standard, as some examples of foreign good practice are also mentioned. The work was prepared with students preparing for the Earthquake Engineering exam in mind and covers the basic spectrum of content in this field. The work discusses all the necessary and sufficient rules and requirements of the standard for solving tasks in the exams in this subject. However, it is necessary to be aware that the problems encountered by the engineer in his professional practice require to deepen and expand this knowledge, as the content shown here represent the firm basis of the subject matter, but not the whole. The core of the material is thus dedicated to the preparation of an appropriate computational model of the building structure, its analysis to obtain data relevant to the calculation of seismic impact, as well as the distribution of seismic impact on the load-bearing elements of the structure.